A study of energy efficiency, economic and environmental benefits of a cooling tower - Saidur, Rahman; Abdelaziz, E.A.; Hasanuzzaman, M.; Mamun, M.A.H. (International Journal of Mechanical and Materials Engineering, 2010)
Cooling tower is one of the most important utilities in industrial and residential facilities. This paper estimates the energy efficiency, economic and environmental benefits of cooling tower. Energy-saving measures by using the high efficient motors and variable speed drive (VSD) were applied to save energy. By installing VSD in the cooling tower's fans, annual energy saving have been found to be 202,972 kWh and potential emissions reduction is about 120 ton of CO 2, 661 kg of SO 2, 312 kg of NO xand 661 kg of CO at different cooling load. By using high efficient motor, emissions reduction are about 6.97 ton of CO 2, 38,400 kg of SO 2, 18,109 kg of NO x and 4,601 kg of CO at 50 load. A sizeable amount of utility bill can be saved by using high efficient motors and applying VSDs. Payback periods for different energy savings measures have been estimated and found to be economically viable.